Ptosis: Evaluation and management - Marian Pauly; R Sruthi (Kerala Journal of Ophthalmology, 2019)
Blepharoptosis, or ptosis of the eyelid, refers to drooping of the upper eyelid that usually results from a congenital or acquired abnormality of the muscles that elevate the eyelid. Ptosis may be the presenting sign or symptom of a serious neurologic disease. Regardless of the etiology, when ptosis obstructs vision, it is disabling. The appropriate management requires recognition of the underlying cause. This review article highlights the various aspects of ptosis evaluation and management.